Responses of Bones, Kidneys and Parathyroid Glands in Wistar Rats Fed Containing Variation of Phosphor Levels - Hartiningsih .; Sutjipto Nitisuwirjo; Hastari Wuryastuty (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2013)
Abstract The objective of the research was to study the responses of bones, kidneys and parathyroid glands of calcium homeostasis in the Wistar rats fed containing variation of phosphor levels. Twenty female Wistar rats at 40 days of age were randomly divided into four groups (A, B, C and D) of five each. The group A was fed diet containing Ca:P ratio = 1.5:1 (diet I/control). The ratio of calcium and phosphorus was 1.5:3 (diet II), 1.5:6 (diet III) and 1.5:9 (diet IV) and were given to the rats in groups B, C, and D, respectively. Each of the rats was placed into individual cages. All of rats were fed diet for 12 weeks and water was provided ad libitum. At the end of the study, blood was collected from the heart for calcium and phosphor analysis, while parathyroid glands, kidneys and left femurs were collected and routinely stained with hematoxylin and eosin for histopathological examination. In the present study, the diet containing Ca:P = 1.5:6 caused decrease of blood calcium, whereas the diet containing Ca:P = 1.5:9 caused decrease of blood calcium and increase of blood phosphorus. Histopathological examination of the parathyroid glands of the rats in group A showed normal structure. The parathyroid glands of the rats in groups B, C and D showed vacuoles in principle cells of the parathyroid glands. The increase of the vacuoles in the principle cells of the parathyroid glands was higher than that of rats in groups B, C and D, respectively. Histopathological examination of kidneys of rats in group A showed normal structure, whereas kidneys of rats in groups B and C and D showed metastatic calcification of renale tubules. The kidneys of rats in groups C and D showed metastatic calcification of the inner and outer layers of tubule lumen, atrophy and necrosis in the epithelial cells of renal tubules, fibroblasts proliferation in interstitial cells, and infiltration of mesangial cells. The kidneys of rats in group D showed proliferation in the epithelial cells of the glomeruli as well. Histopathological examination of metaphysis of proximal femurs of rats in group A showed normal structure, whereas metaphysis of proximal femurs of the rats in groups B, C and D had osteoclasts infiltration, and fibroblasts were predominantly seen in the bone cortex. The increase of osteoclasts in the bone cortex in rats in groups B, C and D was higher than that of rats in group A. The fibroblasts proliferation in the bone cortex was higher in rats in groups C and D. Based on the results of the present study, it was concluded that the diet containing Ca:P = 1.5:3 caused decrease of blood calcium and . The diet containing Ca:P = 1.5:6 caused decrease of blood calcium, hyperplasia of parathyroid glands, , acute nephrosis, and fibrous osteodystrophy. The diet containing Ca:P = 1.5:9 caused decrease of lood calcium and increased of blood phosphorus, hyperplasia of the parathyroid glands, chronic glomerulonephritis and fibrous osteodystrophy.